Designation of a lectotype for the Canestrini's Goby, Gobius canestrinii Ninni, 1883 (Teleostei, Gobiiformes, Gobiidae, Gobionellinae) - Ahnelt, Harald (Array, 2021)
A recent study based on molecular biological data revealed that Gobius canestrinii (Ninni, 1883), a gobioid fish endemic to the Adriatic basin, has to be split in three lineages. The original description was based on populations from two distant localities in Italy and in Croatia respectively, the first representing one of these lineages, the second most likely belonging to another lineage. To fix the name of the species, we hereby designated a lectotype for Canestrini"s Goby.